In vitro vascular differentiation system efficiently produces natural killer cells for cancer immunotherapies - Yekaterina Galat; Yuchen Du; Mariana Perepitchka; Xiao-Nan Li; Irina V Balyasnikova; William T Tse; Svetlana Dambaeva; Sylvia Schneiderman; Philip M Iannaccone; Oren Becher; Douglas K Graham; Vasiliy Galat (OncoImmunology)
Background Immunotherapeutic innovation is crucial for limited operability tumors. CAR T-cell therapy displayed reduced efficiency against glioblastoma (GBM), likely due to mutations underlying disease progression. Natural Killer cells (NKs) detect cancer cells despite said mutations – demonstrating increased tumor elimination potential. We developed an NK differentiation system using human pluripotent stem cells (hPSCs). Via this system, genetic modifications targeting cancer treatment challenges can be introduced during pluripotency – enabling unlimited production of modified “off-the-shelf” hPSC-NKs.Methods hPSCs were differentiated into hematopoietic progenitor cells (HPCs) and NKs using our novel organoid system. These cells were characterized using flow cytometric and bioinformatic analyses. HPC engraftment potential was assessed using NSG mice. NK cytotoxicity was validated using in vitro and in vitro K562 assays and further corroborated on lymphoma, diffuse intrinsic pontine glioma (DIPG), and GBM cell lines in vitro.Results HPCs demonstrated engraftment in peripheral blood samples, and hPSC-NKs showcased morphology and functionality akin to same donor peripheral blood NKs (PB-NKs). The hPSC-NKs also displayed potential advantages regarding checkpoint inhibitor and metabolic gene expression, and demonstrated in vitro and in vivo cytotoxicity against various cancers.Conclusions Our organoid system, designed to replicate in vivo cellular organization (including signaling gradients and shear stress conditions), offers a suitable environment for HPC and NK generation. The engraftable nature of HPCs and potent NK cytotoxicity against leukemia, lymphoma, DIPG, and GBM highlight the potential of this innovative system to serve as a valuable tool that will benefit cancer treatment and research – improving patient survival and quality of life.